Progress of PD-1/PD-L1 signaling in immune response to liver transplantation for hepatocellular carcinoma - Ju, Feng; Wang, Dawei; Huang, Lan; Jiang, Chun; Gao, Ce; Xiong, Cunquan; Zhai, Guanghua (Frontiers in Immunology, 2023)
Primary liver cancer is one of the most common malignant tumors in China. The vast majority of primary liver cancer are hepatocellular carcinoma. Due to its high incidence and mortality from HCC, HCC has always been a feared type of cancer. Liver transplantation, as one of the important means to treat advanced liver cancer, has brought new hope to patients. However, as patients have been in a state of immunosuppression after liver transplantation, these patients face new problems of HCC recurrence and metastasis. A increasing number of studies have proved that blocking the PD-1/PD-L1 signaling pathway and restoring the immune killing inhibition of T cells can produce better therapeutic effects on tumors and chronic infectious diseases. As a promising treatment in the field of tumor immunotherapy, PD-1/PD-L1 inhibitors have achieved important results in liver cancer patients, but their application in liver transplantation patients is still highly controversial. This paper will introduce the mechanism of action of PD-1/PD-L1 signaling pathway and the current basic and clinical studies of PD-1/PD-L1 signaling pathway associated with immune response in HCC transplantation.